On Some Values of the Sandor-Smarandache Function - Islam, S. M. S.; Majumdar, A. A. K. (Journal of Scientific Research, 2022)
The Sandor-Smarandache function, due to Sandor, has drawn the attention of the researchers soon after its introduction. The new Smarandache-type arithmetic function, denoted by SS (n), involves binomial coefficients. Sandor found SS(n) when n ( ³ 3) is an odd integer. It has been shown that the function has a simple form even when n is even and not divisible by 3. In earlier papers, some closed-form expressions of SS(n) have been derived for particular cases of n. Still, some unexplored results are needed to settle down the function. So, this study finds more forms of SS(n), starting from the function SS(24m). Particular attention has been focused on the functions SS(120m), SS(840m), SS(9240m) and SS(120120m).